Evaluation of the effect of the indoor environment on the physiological responses of early-gestation sows in a commercial house in China - Li, Yangyang; Li, Tong; Shang, Bin; Zhao, Yang; Tao, Xiuping; Peng, Feng; Zou, Xiaojun; Zhang, Sixin (Frontiers in Veterinary Science, 2023)
Objective The environment influences the sow's health and physiology during gestation. This study was conducted to evaluate indoor environmental parameters and physiological responses of early-gestation sows and investigate the possible methods for assessing the thermal environment in commercial houses. Methods A total of 20 early-gestation sows (commercial purebred Yorkshire) with an average body weight of 193.20 ± 3.62 kg were used for this study in winter, spring, summer, and autumn. The indoor environment parameters comprising dry-bulb temperature (Tdb), relative humidity (RH), and carbon dioxide (CO2) were recorded in 30-min intervals. Physiological parameters including heart rate (HR) and respiration rate (RR) of sows were also measured every 30 min. Wet-bulb temperature (Twb) was calculated using Tdb, RH and atmospheric pressure was recorded at a nearby weather station. Results The average indoor Tdb and RH were 12.98 ± 2.03°C and 80.4 ± 6.4% in winter, 18.98 ± 2.68°C and 74.4 ± 9.0% in spring, 27.49 ± 2.05°C and 90.6 ± 6.4% in summer, and 17.10 ± 2.72°C and 64.5 ± 10.9% in autumn. A higher average concentration of CO2 was observed in winter (1,493 ± 578 mg/m3) than in spring (1,299 ± 489 mg/m3), autumn (1,269 ± 229 mg/m3), and summer (702 ± 128 mg/m3). Compared with the HR and RR in the optimum environment, high RH in the house led to a significant decrease in both HR and RR (P < 0.05). In addition, a significant decline in HR was also obtained at high temperatures (P < 0.05). A temperature humidity index (THI), THI = 0.82 × Tdb + 0.18 × Twb, was determined for early-gestation sows, and the THI thresholds were 25.6 for HR. The variation in THI in summer showed that heat stress still occurred under the pad-fan cooling system. Conclusion This study demonstrated the critical significance of considering physiological responses of early-gestation sows in commercial houses and THI thresholds. We recommend that much more cooling measures should be taken for early-gestation sows in summer.